Pembangunan Desa Berkelanjutan: Inovasi Kolaborasi Program Masagi Bersih - Maharani, Hapsari Kharisma; Abubakar, Rodlial Ramdhan Tackbir (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
The sustainable development program is one of the national programs which is carried out intensively based on the mandate of Presidential Regulation Number 59 of 2017 concerning Implementation of Sustainable Development Goals. Thus, every region in Indonesia, starting from the province to the village, is obliged to implement this sustainable development program. However, based on SDGs data, Indonesia’s ranking among 116 countries is still low. In fact, Indonesia’s rating has decreased from 98 in 2016 to 101 in 2020. Therefore, it is necessary to develop an ideal and integrated design collaboration pattern to build a collaborative process between the government and other stakeholders. The aim of this research is to design a collaborative innovation design between the Ciburial Village Government and local entrepreneurs to support the development of Ciburial Village in accordance with the Concept of Sustainable Development. This study uses a qualitative method which is expected to provide an overview of the collaborative process of the Masagi Bersih Program carried out by the government of Ciburial Village, Cimenyan District, Bandung Regency and then analyze it using the Collaborative Governance pattern from (Ansell and Gash 2008). Data collection was carried out through interviews and observations with the village government, BPD, local entrepreneurs and the community totaling 7 persons. Based on the results of the research, it is shown that the development of collaboration patterns is emphasized on face-to-face communication processes that need to be carried out to obtain agreements that will have an impact on increasing commitment, trust, results, and understanding obtained.